Pain severity and pain control following intracranial surgery - A, Saringcarinkul; P, Pin-on; N, Chiratthanapong; S, Chuasuwan; P, Sattayopas (Biomedical Sciences and Clinical Medicine, 2019)
Objective To explore the incidence and severity of acute post-craniotomy pain in Maharaj Nakorn Chiang Mai Hospital, including the adequacy of routine pain relief practices. Methods Postoperative analgesia prescribed for patients undergoing elective intracranial surgery was classified into two surgical groups: the supratentorial and the infratentorial approaches. Demographic and perioperative clinical data, including the use of a scalp block and the dosage of fentanyl, were collected and analysed. Postoperative pain was assessed for three days following surgery using a numeric rating scale (NRS) or a revised non-verbal pain scale (NVPS-R). Pain medication treatment and side effects were recorded. Results Of 251 patients, 190 underwent a supratentorial craniotomy, while 61 were treated with an infratentorial approach. On the first postoperative day, the incidence of a NRS score ≥4 (moderate to severe pain) was 18.2-31.8% with NRS versus 6.4-11.1% for NVPS-R. The incidence of a pain score of zero gradually increased over time, reaching 100% in patients assessed with NVPS-R and 87% in those with NRS on day three. In the infratentorial group, a pre-incisional scalp block decreased pain scores upon arrival at the ward and for the first four-hour period after surgery (p=0.05 and 0.042, respectively). Over 90% of patients were prescribed intravenous tramadol every six hours on postoperative day one, but only 60% were given tramadol during the first 8-16 hours in the supratentorial group, while 75% of the infratentorial group received tramadol (p=0.021). Conclusion Pain after intracranial surgery was effectively relieved with tramadol. NVPS-R should be investigated further to confirm its reliability as a tool for non-verbally communicating patients.